Development of a Cutting Edge Temperature Measurement Device for End Mill Tool using Infrared Radiation Technique - Mohammad Ashaari, Kiprawi (Universiti Malaysia Sarawak (UNIMAS), 2020)
In current times, high speed machining (HSM) is no stranger in the manufacturing industry. It is also a fact that temperature plays an important role in productivity every process where HSM is involved. Therefore, it is vital for manufacturers to monitor the cutting temperature but this has been proven to be quite challenging due to difficulty of determining cutting temperature at high cutting speed. This research focused on the relationship between the infrared radiation of an object to its temperature and the application of its theory to develop an accurate temperature measuring device, which is also known as a pyrometer. The developed pyrometer used a fiber optic to harness infrared radiation which was channeled to a photocell and converts it to electrical signal. The electrical signal was amplified and can be seen on a digital oscilloscope. A calibration experiment was conducted to identify the relationship between output voltage on the oscilloscope and the temperature. The developed pyrometer was used in an experiment which involves actual cutting to determine the effect of radial depth of cut on cutting temperature in different cutting speed. For each depth of cut, the temperatures were analysed and compared for different cutting speed. Based on the data from the experiment, it can be seen that as radial depth of cut increases, the cutting temperature increases. The same trend can be seen when the cutting speed is increased which shows a significant rise of cutting temperature.